TUJUAN PENDIDIKAN MENURUT AL-QURAN - M. Yemmardotillah (El-Rusyd, 2016)
he Humans were created by Allah SWT with the potential. of coursewith a very precise reason that potential must be present in humans, as hasbeen known to man was created to be khalifatullah fil ard. The potential of thehuman being has no meaning if it were not for the guidance and the guidanceof Allah who served in nature. However, humans are not also just able toswallow what is seen, but to learn to drive all the power those to be able tounderstand the signs that exist in this life. Based on the considerations above,Islam has given huge attention to the purpose of education.The Quran tells a lot about education and the urgency for human life.In essence, the entire paragraph contained in the Koran contain educationalvalues that are beneficial for those who study and dig with a mind potentialpossessed. This goal is the outcome of all of the educational process is carriedout. Similarly, the Koran, has also outlined the goals of education as thedirection to go by every individual Muslim in taking his life on earth. With thepurpose of education in the Koran, it means every Muslim own orientation isvery clear and steady and level of higher consciousness.